Recovery and properties of oil from the copepod Calanus finmarchicus - Vang, Birthe (UiT The Arctic University of Norway, 2016)
The papers of this thesis are not available in Munin. Paper I. Oil extraction from the copepod Calanus finmarchicus using proteolytic enzymes. Vang, B., Pedersen, A. M., & Olsen, R. L. Available in Journal of Aquatic Food Product Technology, 22:6, 2013, pp. 619-628. Paper II. Detection of tropomyosin and determination of proteins in crustacean oils. Vang, B., Mæhre, H. K., Jensen, I-J. & Olsen R. L. Available in Food Chemistry, 141:1, 2013, pp. 72–76. Paper III. Oil from Calanus finmarchicus - Composition and Possible Use: A Review. Pedersen, A. M., Vang, B., & Olsen, R. L. Available in Journal of Aquatic Food Product Technology, 23:6, 2014, pp. 633-644. The limited amount of fish oils available has led to extensive search for alternative sources of oils rich in health beneficial long-chain polyunsaturated ω-3 fatty acids. The zooplankton Calanus finmarchicus, also known as redfeed, is present in large amounts in the North Atlantic and has lipid-rich stages, which can be harvested. One of the main objectives of this study was to investigate if the use of proteolytic enzymes could improve oil recovery from C. finmarchicus in an industrial-like process, and to characterize the oil obtained. The results showed a substantially higher oil yield with the use of proteolytic enzymes compared to standard fish oil production technology. The oil from C. finmarchicus was rich in the powerful antioxidant astaxanthin and had a high content of the ω-3 fatty acids, mainly found as wax esters. The wax ester rich oil is well utilized by fish, and recent reports indicate that Calanus oil may have beneficial health effects beyond those, which may be ascribed to intake of ω-3 fatty acids alone. Tropomyosin is known to be the main allergen in crustaceans and another objective was to investigate if this protein could be detected in Krill and Calanus oils. Tropomyosin was not detected in Calanus oil probably due the production method. A method for accurate determination of the protein content in oils by direct amino acid ...